Developed meloxicam loaded microparticles for colon targeted delivery: Statistical optimization, physicochemical characterization, and in-vivo toxicity study. - Syed Abdul Wasay; Syed Umer Jan; Muhammad Akhtar; Sobia Noreen; Rahman Gul (PLoS ONE, 2022)
The study aimed to fabricate and evaluate Meloxicam (MLX) loaded Hydroxypropyl Methylcellulose (HPMC) microparticles for colon targeting because MLX is a potent analgesic used in the treatment of pain and inflammation associated with colorectal cancer (CRC). Nevertheless, its efficiency is limited by poor solubility and gastrointestinal tracts (GIT) associated side effects. Seventeen formulations of MLX loaded HPMC microparticles were fabricated by the oil-in-oil (O/O)/ emulsion solvent evaporation (ESE) technique. A 3-factor, 3-level Box Behnken (BBD) statistical design was used to estimate the combined effects of the independent variables on the dependent variables (responses), such as the percent yield (R1), the entrapment efficiency (EE) (R2), mean particle size (R3) and in vitro percentage of cumulative drug release (R4). For physicochemical characterization FTIR, XRD, DSC, and SEM analyses were performed. Biocompatibility and non-toxicity were confirmed by in-vivo acute oral toxicity determination. The percentage yield and EE were 65.75-90.71%, and 70.62-88.37%, respectively. However, the mean particle size was 62.89-284.55 μm, and the in vitro cumulative drug release percentage was 74.25-92.64% for 24 hours. FTIR analysis showed that the composition of the particles was completely compatible, while XRD analysis confirmed the crystalline nature of the pure drug and its transition into an amorphous state after formulation. DSC analysis revealed the thermal stability of the formulations. The SEM analysis showed dense spherical particles. The toxicity study in albino rabbits showed no toxicity and was found biocompatible. The histopathological evaluation showed no signs of altered patterns. Results of this study highlighted a standard colonic drug delivery system with the ability to improve patient adherence and reduce GIT drug-associated side effects in CRC treatment.